Home learning environment across time: the role of early years HLE and background in predicting HLE at later ages. Issue 1 (2nd January 2020) - Toth, Katalin; Sammons, Pam; Sylva, Kathy; Melhuish, Edward; Siraj, Iram; Taggart, Brenda
ABSTRACT: This study explores how various measures of home learning environment (HLE) collected at different ages are related to each other and explores associations when the effects of significant child and family characteristics are controlled for. Different age-appropriate measures of the HLE were constructed at ages 3, 7, 11, and 14. The measures were derived from parents' reports (3, 7, and 11), but at age 14 both adolescents' self-reports and parents' questionnaires responses were used. Multilevel models tested the effects of earlier measures of HLE on later measures, while the same set of individual and family characteristics were controlled. The early years HLE measure was a significant predictor of later measures of HLE across different phases of education (primary and secondary school). The strength of the relationships between different HLE measures depended on the time lag between measurements but also on the nature of the activities covered in each dimension.